Pengaruh Latihan Passing Bawah Dengan Metode Berhadapan Terhadap Peningkatan Teknik Passing Bawah Bola Volly Pada Siswa Ekstrakurikuler Smp Negeri 01 Bermani Ilir - Melan Afriansah; Asnawati Asnawati; Deffri Anggara (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine and analyze the effect of underhand passing training with the facing method on improving the underhand passing technique of extracurricular students of SMP Negeri 01 Bermani Ilir. This study is a study with experimental treatment. The sample in this study was 20 extracurricular students of SMP Negeri 01 Bermani Ilir. Data collection techniques were by means of tests and measurements and observations, data analysis was the significance test